Penentuan Model Isoterm Adsorpsi Ion Cu(II) Pada Karbon Aktif Tempurung Kelapa - Khamaluddin Aditya; Yusnimar Yusnimar; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Copper metal (Cu2+) pollution gives bad impact for society life. One effort to reduce the content of copper metal by using adsorption process. This research used physical activationmethod with temperature at 700oC for 3 hours. This research purpose is to determine the absorptive capacity of the coconut shell activated carbon adsorption and the appropriateadsorption isotherm models. A total of 1 g of coconut shell activated carbon mixed with a solution of CuSO4 with a volume of 100 ml at various concentrations (10, 15, 20, 25 and 30ppm). Then the solution was analyzed by AAS to determine the concentration of Cu ion remaining. The Results showed that the ion adsorption of Cu (II) by a coconut shell activatedcarbon reached equilibrium after a contact time of 90 minutes, and adsorption occured by following the Freudlich adsorption models with correlation coefficient (R2) was 0.9848 and the maximum value of adsorption was 99,96 % mg Cu (II) / g adsorbent.Keywords : Activated Carbon, Adsorption, Ion Cu(II), Coconut Shell and Physics Activation